Flora vascular dos banhados do Parque Natural Municipal da Ronda, São Francisco de Paula, Rio Grande do Sul, Brasil - Barbieri, Fabrícia (2023)
The definition of bogs involves several factors, and the presence of aquatic macrophytes, flora species adapted to these environments, an indicator for the characterization of these areas. The present study aimed to carry out a floristic survey in four wetlands in the Parque Natural Municipal da Ronda (PNMR), São Francisco de Paula, RS, in order to enrich the knowledge about the local biodiversity present in this conservation unit. Sampling was carried out through expedited walking, covering all identified micro-habitats. Each species observed in flowering or fruiting was photographed and collected for herborization, later identified and deposited in the herbarium. 104 species representing 36 botanical families were recorded, the richest being Asteraceae (n=18), Poaceae (n=13) and Cyperaceae (n=11). 67 genera were identified, with the greatest floristic richness Baccharis and Habenaria (5 spp. each), Rhynchospora, Paspalum and Xyris (4 spp. each), Eryngium, Eleocharis, Hypericum, Utricularia (3 spp. each). It was possible to record the presence of eight species with some degree of extinction threat at the state and federal levels. This study, in addition to bringing the enrichment of the biodiversity of the wetlands flora to the region, also identified and characterized these areas as bogs, considered Permanent Preservation Areas, within the PNMR area.